Isolation and cloning of ABCF1 gene from Rasbora Sarawakensis - Clarissa, Patrick Balinu (Universiti Malaysia Sarawak, (UNIMAS), 2016)
Ribosome assembly and protein translation process are regulated by ABCF1 gene. Since the function of ABCFI gene is ribosome assembly regulation, the loss of this function may cause the failure to make proteins in an organism. The purpose of this study is to clone the ABCFI gene of Rasbora sarawakensis into pGEM-T easy vector and analyse the extracted gene sequence from R. sarawakensis. Total RNA was extracted from a whole fish homogenate via Tri reagent and phenol chloroform precipitation. The cDNA generated from reverse transcription was amplified with PCR using degenerate primers targeting the conserved region of the gene. The PCR amplified amplicons of size approximately 803 bp and was inserted into pGEM-T easy vector. Transformation was performed using in-house prepared E. coli JM109 competent cell which has the efficiency of 1.57 x 104 transformants/μg. The white colonies were run in colony PCR and confirmed to have an insert. Further confirmation was conducted by performing Nod restriction digestion and the result shows two discreet bands. Afterwards, the plasmid that was obtained from plasmid miniprep was sent for sequencing and the result was corroborated by using BLAST and it shows highest similarity to gene of Sinocyclocheilus anshuiensis. Based on this study, further study of expression analysis can be conducted which can lead to the understanding of the temporal and spatial patterns of gene expression that can help assign function to genes, thus establishing R. sarawakensis as a model of study to detect eco-toxicity of Sarawakian rivers.